Strengthening the Reproductive Endocrinology and Infertility Curriculum Through Three Interactive Cases - Molly Siegel Kornfield; Elizabeth Rubin; Pamela Parker; Bharti Garg; Amy Stenson; Paula Amato; Sacha Krieg (Association of American Medical Colleges, 2023)
Introduction Improved reproductive endocrinology and infertility (REI) curricula are needed to address educational deficiencies both at our institution and on a national level. To improve REI education for OB/GYN residents and medical students, we developed and piloted a curriculum with in-person and virtual flexibility. Methods We developed three clinical vignettes for a facilitator-led case-based discussion among OB/GYN residents: two office cases and one emergency scenario. Cases were evaluated by content experts and tested before implementation. Pre- and postsurveys included both multiple-choice questions on content and a Likert-scale self-assessment of comfort, satisfaction, and knowledge. Postsurveys were administered immediately postintervention and at a delayed interval. Responses were compared using paired t tests and McNemar tests. Results Eighteen learners (16 OB/GYN residents and two medical students) participated, the majority in person, of whom 17 (94%) completed a postsurvey. Self-rated proficiency in evaluating and managing irregular menses, infertility, and amenorrhea all improved significantly immediately following the intervention (p < .05 for all). Learners reported significantly more knowledge and comfort with REI compared to other subspecialties following the intervention (p < .05). More learners responded correctly to knowledge questions postintervention (p < .05 for questions 1 and 2, p = .16 for question 3). All learners were satisfied with and enjoyed the curriculum. Eight learners completed the delayed postsurvey and showed sustained improvements in knowledge and competence with REI content. Discussion Facilitator-guided case-based learning was effective in improving learners' confidence, comfort, and knowledge in managing REI conditions, and improvements were sustained following a delayed interval.